Ponudba in razvoj ne dohajata povpraševanja - Ločniškar-Fidler, Mateja (Šolska knjižnica, 2012)
Slovenian market is seeing an increasing number of publishers offering electronic books. Also the first Slovenian electronic publisher has been announced with initial offer of 250 book titles. School libraries and public libraries regularly follow the offer in the market. Thus e-books have been included in many library collections, but the library system COBISS does not meet the new demands. Thus libraries in many cases have to manually catalogue e-books. Libraries also warn that library compensation sum, received yz Slovenian authors, only tales into account printed books. Access to e-books is different n different libraries. The paper presents in detail the loan of e-books on readers in Municipial Library of Ljubljana which was a pioneer in this service in Slovenia. The paper concludes with a presentation of some current readers.
Keywords: bralniki; COBISS; e-knjige; ponudba; Slovenija; splošne knjižnice; šolske knjižnice; založbe